Susceptibility and Target Organ of Lymphocystis Disease Virus Infection in Giant Gourami (Osphronemus goramy), Hybrid Tilapia (Oreochromis sp.), Siamese Fighting Fish (Betta splendens), and Hybrid Catfish (Clarias sp.) - Nikmah, Nur Lailatul Fitrotun; Isnansetyo, Alim; Istiqomah, Indah; Murwantoko, Murwantoko (Jurnal Ilmiah Perikanan dan Kelautan, 2024)
Highlight Research 1. Lymphocystis disease is reported to infect seawater and freshwater fishes 2. The four important freshwater fish species in Indonesia are evaluated on their susceptibility to Lymphocystis Disease Virus 3. Lymphocystis infection causes behavioural changes and mortality with different onset times after infection on the four fish species 4. LCDV load is varied in quantity among different organs. Abstract Lymphocystis disease has a broad host range and has been reported to enter Indonesia. However, information regarding its susceptibility and predilection organs in fish is lacking. This study examined the susceptibility of four important fish species in Indonesia, namely, giant gourami (Osphronemus goramy), hybrid tilapia (Oreochromis sp.), Siamese fighting fish (Betta splendens), and hybrid catfish (Clarias sp.). The fish were infected with virus filtrate by intraperitoneal injection and immersion. The postinfection observation period was 60 days. Viral load was quantified by qPCR and expressed as major capsid protein (MCP) copy number/mg tissue. Mortality was observed in all fish species, with the highest recorded in hybrid catfish and the lowest in Siamese fighting fish. All the fish species showed changes in their clinical symptoms, such as anorexia and separation from schools. However, only giant gourami showed internal change seven days after injection (dpi), with white lesion detected in the liver. Viral load quantification showed that LCDV had different predilection organs in the four fish species. The highest viral load of giant gourami (1.7 x 104) was observed in the liver at 7 dpi, hybrid tilapia (7.5 x 103) was observed in the fins at 21 dpi, Siamese fighting fish (8.4 x 103) was observed in the fins at 14 dpi, and hybrid catfish (1.2 x 103) were observed in the fins and gills at 7 and 14 dpi. The findings indicated that giant gourami, hybrid tilapia, Siamese fighting fish, and hybrid catfish were susceptible to LCDV infection with different predilection organs.